Plant Essential Nutrients and Their Role - Lakesh K. Sharma; J. Mabry McCray; Kelly Morgan (EDIS)
The purpose of this publication is to inform Extension agents, consultants, and farmers about plant essential nutrients, benefits, and deficiency symptoms. This publication provides a whole plant picture with deficiency symptoms for each nutrient and the location of those symptoms on the plant. Written by Lakesh K. Sharma, J. Mabry McCray, and Kelly Morgan, and published by the UF/IFAS Agronomy Department, May 2022.